Early diagnosis of kidney cancer by computed tomography imaging – a case study - Wróbel, Grzegorz (Journal of Education, Health and Sport, 2018)
In the case of small tumors, the kidneys usually do not show the oncological importance and are characterized by slow growth, however, the presence of any changes that occur within these tumors should be monitored. A 66-year-old man underwent computed tomography (CT) examination. As a result of the study, in the lower pole of the left kidney, a tumor mass was observed. Imaging studies performed for various reasons often show an abnormal mass within the kidneys. The reasons for the development of kidney tumors are not fully understood.